Clinical profile of congenital hypothyroidism identified through new-born screening: a retrospective observational study - Palanisamy, Sudhakar; Srinivasan, Ramesh (International Journal of Contemporary Pediatrics, 2020)
Background: Congenital hypothyroidism is one of the most common preventable causes of mental retardation. The incidence and etiology of congenital hypothyroidism varies significantly across the globe. Methods: In this retrospective observational study we aimed to find out the incidence and etiology of congenital hypothyroidism identified by neonatal screening program. We included all neonates who had their thyroid stimulating hormone screening done in a tertiary care hospital of South India between January 2014 and June 2020 and were diagnosed as a case of congenital hypothyroidism. The growth patterns, clinical features, thyroxine dose requirement during follow-up were also studied. Results: There were 23 babies diagnosed with congenital hypothyroidism during the study period. The incidence rate was 1 in 917 live births for inborn babies, and dyshormogenesis (60%) was the most common etiology. Two babies had clinical features associated with congenital hypothyroidism. None of the babies had clinical features of congenital hypothyroidism during follow-up and their growth & development were normal for age. Babies who required dose increments of thyroxine supplement turned out to be permanent congenital hypothyroidism. Conclusion: Incidence of congenital hypothyroidism was high in our population. Dyshormogenesis was the most common etiology. Majority of congenital hypothyroidism babies were asymptomatic at diagnosis, so screening is a vital tool for early diagnosis. Babies who required thyroxine dose increment with age tend to be permanent congenital hypothyroidism.